2013
DOI: 10.1016/j.pbb.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The periaqueductal gray contributes to bidirectional enhancement of antinociception between morphine and cannabinoids

Abstract: Co-administration of opioids and cannabinoids can enhance pain relief even when administered on different days. Repeated systemic administration of morphine has been shown to enhance the antinociceptive effect of tetrahydrocannbinol (THC) administered 12 hours later, and repeated microinjection of the cannabinoid receptor agonist HU-210 into the ventrolateral periaqueductal gray (PAG) has been shown to enhance the antinociceptive effect of morphine administered one day later. The primary objective of the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…It is noteworthy, however, that many other neurotransmitter systems (e.g., serotonin [52], opioids [53,54], cannabinoids [17,55], etc.) located within the PAG have also been implicated in the modulation of nociception and various forms of stress-induced antinociception.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy, however, that many other neurotransmitter systems (e.g., serotonin [52], opioids [53,54], cannabinoids [17,55], etc.) located within the PAG have also been implicated in the modulation of nociception and various forms of stress-induced antinociception.…”
Section: Discussionmentioning
confidence: 99%
“…Allosteric modulators of CB 1 receptors may therefore be a useful strategy for amplifying effects of ECs only at sites where they are produced and released on demand (Laprairie et al, 2017). Nonetheless, multifunctional compounds targeting the ECS allied to inhibition of COX2 (Grim et al, 2014), antagonism of TRPV1 (Maione et al, 2006; or in combination with opioids (Wilson-Poe et al, 2013) or non-steroidal anti-inflammatory drugs (Guindon et al, 2006) have great potential to produce a superior therapeutic profile with minimized unwanted cannabimimetic side effects. A novel therapeutic approach in many pathological states can be the possible modulation of EC activity through the regulation of their synthesis or degradation.…”
Section: Figure 10mentioning
confidence: 99%
“…Pharmacological treatment of orofacial pain is difficult and controversial (Tzabazis et al, 2014;Weiss et al, 2017). It has been demonstrated that the endogenous opioid system could be involved in cannabinoid antinociception, and recent data have also provided evidence for a role of the endogenous cannabinoid system in opioid antinociception (Cichewicz, 2004;Bushlin et al, 2010;Wilson-Poe et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that a dual pharmacotherapy at these targets may increase CB-mediated analgesic effects [13][14][15][16]. For example, the CB1 agonist THC shows synergistic effects with sub-analgesic doses of the μ-opioid agonist morphine in a rat arthritic pain model [17].…”
Section: Introductionmentioning
confidence: 99%